Penerapan Media Audio Visual dalam Pembelajaran Bahasa Arab di Kelas VII Madrasah Tsanawiyah Nurul Jadid Pandaan Pasuruan - Khalifah (Universitas Yudharta Pasuruan, 2017)
Audio visual Media in learning Arabic, is one of the essential components that have the same position with the other components. The accuracy of teachers in choosing and using media learning very beneficial against the effectiveness of delivered subject matter to students and influence on student achievement. The purpose of this research is to know the influence of the audio visual media in learning Arabic in grades VII middle school An-Nurul Jadid Pandaan Pasuruan and to know the factors that become advocates and a barrier against the application of audio visual media in learning Arabic in grades VII middle school An-Nurul Jadid Pandaan Pasuruan. Research results exposed that the influence of audio visual media in learning Arabic in grades VII middle school An-Nurul Jadid Pandaan Pasuruan felt quite help students to achieve the indicators of the Arabic language. Factors restricting the application of audio visual in Arabic language learning in Class VII middle school An-Nurul Jadid Pandaan Pasuruan is a condition of financial schools haven't allowed against the procurement of means of learning in the form of audio-visual media. While supporting the application of audio visual factors in learning Arabic is the professionalism of teachers, the student's enthusiasm toward learning the use of audio visual media.